Pemberian Duddingtonia flagrans dan Saccharomyces cerevisiae Meningkatkan Produksi Susu dan Menurunkan Populasi Cacing pada Sapi (THE TREATMENT OF DUDDINGTONIA FLAGRANS AND SACCHAROMYCES CEREVISIAE INCREASE MILK PRODUCTION AND DECREASE WORM POPULATION IN - Ahmad, Riza Zainuddin; Gholib, Djaenudin (Jurnal Veteriner, 2014)
Duddingtonia flagrans isolates are commonly used as biological control, and Saccharomyces cerevisiaeas probiotics. This study aimed to test isolates D. flagrans and S. cerevisiae as a biological agent andprobiotics. Tests carried out on beef cattle and dairy cows, which grouped into treatment (Administrationof D. flagrans and S. cerevisiae) and controls. For examination worm was also made in the grass. The studywas done in seven months The results of this study indicate that there is increase of 10 to 15% of the milkproduction in dairy cows after treatment (p> 0.05) but the beef was no difference between the treatmentand control. Treatment of D. flagrans significantly reduced the population of worms in the grass andanimals. Base on the result, it was concluded that D. flagrans and S. cerevisiae can be used together toincrease milk production and reduce the population of worms in cattle.
Keywords: Duddingtonia flagrans, Saccharomyces cerevisiae, production, worm